EV-mediated promotion of myogenic differentiation is dependent on dose, collection medium, and isolation method - Britt Hanson; Ioulia Vorobieva; Wenyi Zheng; Mariana Conceição; Yulia Lomonosova; Imre Mäger; Pier Lorenzo Puri; Samir El Andaloussi; Matthew J.A. Wood; Thomas C. Roberts (Elsevier, 2023)
Extracellular vesicles (EVs) have been implicated in the regulation of myogenic differentiation. C2C12 murine myoblast differentiation was reduced following treatment with GW4869 or heparin (to inhibit exosome biogenesis and EV uptake, respectively). Conversely, treatment with C2C12 myotube-conditioned medium enhanced myogenic differentiation. Ultrafiltration-size exclusion liquid chromatography (UF-SEC) was used to isolate EVs and non-EV extracellular protein in parallel from C2C12 myoblast- and myotube-conditioned medium. UF-SEC-purified EVs promoted myogenic differentiation at low doses (≤2 × 108 particles/mL) and were inhibitory at the highest dose tested (2 × 1011 particles/mL). Conversely, extracellular protein fractions had no effect on myogenic differentiation. While the transfer of muscle-enriched miRNAs (myomiRs) has been proposed to mediate the pro-myogenic effects of EVs, we observed that they are scarce in EVs (e.g., 1 copy of miR-133a-3p per 195 EVs). Furthermore, we observed pro-myogenic effects with undifferentiated myoblast-derived EVs, in which myomiR concentrations are even lower, suggestive of a myomiR-independent mechanism underlying the observed pro-myogenic effects. During these investigations we identified technical factors with profound confounding effects on myogenic differentiation. Specifically, co-purification of insulin (a component of Opti-MEM) in non-EV LC fractions and polymer precipitated EV preparations. These findings provide further evidence that polymer-based precipitation techniques should be avoided in EV research.